2020
DOI: 10.3390/cancers12092339
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning Intensity, Pre-Transplant Flow Cytometric Measurable Residual Disease, and Outcome in Adults with Acute Myeloid Leukemia Undergoing Allogeneic Hematopoietic Cell Transplantation

Abstract: How conditioning intensity is related to outcomes of AML patients undergoing allografting in morphologic remission is an area of great ongoing interest. We studied 743 patients in morphologic remission and known pre-transplant measurable residual disease (MRD) status determined by multiparameter flow cytometry (MFC) who received a first allograft after myeloablative, reduced intensity, or nonmyeloablative conditioning (MAC, RIC, and NMA). Overall, relapse-free survival (RFS) and overall survival (OS) were long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…Data from 714 of the 810 patients in the final study cohort, including 264 patients examined for early post-HCT MRD clearance after MAC, have been partially reported. 7,[9][10][11][12][13][14][15][16][17] The HCT-specific comorbidity index was calculated as previously described. 18 Related or unrelated donors were selected by high-resolution HLA typing.…”
Section: Study Cohortmentioning
confidence: 99%
“…Data from 714 of the 810 patients in the final study cohort, including 264 patients examined for early post-HCT MRD clearance after MAC, have been partially reported. 7,[9][10][11][12][13][14][15][16][17] The HCT-specific comorbidity index was calculated as previously described. 18 Related or unrelated donors were selected by high-resolution HLA typing.…”
Section: Study Cohortmentioning
confidence: 99%
“…In light of these results that suggest benefits of more intensive conditioning primarily for some or all AML patients who were MRD-positive prior to HSCT, a recent analysis suggested that MAC should also be considered for MRD-negative AML patients if tolerated. 49 In an analysis of 287 patients with MDS, 50 of whom one quarter had >5% marrow blasts and more than a half were MRD-positive at HSCT, as determined by multiparameter flow cytometry and cytogenetics on marrow aspirates, it was found that the risk of overall mortality was higher with lower intensity retimens than with higher intensity regimens among the MRD-positive patients. On the other hand, MRD-negative patients had similar risks of mortality.…”
Section: Measurable Disease Statusmentioning
confidence: 99%
“…In light of these results that suggest benefits of more intensive conditioning primarily for some or all AML patients who were MRD-positive prior to HSCT, a recent analysis suggested that MAC should also be considered for MRD-negative AML patients if tolerated. 49 …”
Section: Factors Which May Be Helpful In the Decision Process: Balance Between The Risk Of Relapse And Non-relapse Mortalitymentioning
confidence: 99%
“…More recently another study confirmed these results [83]. More currently, and in contrast with the above studies, the Fred Hutchinson Cancer Research Center reported that MAC determines longer RFS and OS but similar RR in comparison to RIC and NMA conditioning [84]. Importantly, in MRD+ patients, MAC determined RR and OS similar to RIC and NMA, whereas in MRD− patients, it determined a better clinical outcome in comparison to RIC and NMA (3-y OS and RFS 69% and 71% vs. 47% and 55% for RIC vs. 47% and 52% for NMA; 3-y RR 18% vs. 30% for RIC and NMA).…”
Section: Peri-allohsct Mrd Assessmentmentioning
confidence: 76%